The effects of access restrictions and communication strategies for divisive environmental management. Issue 122 (August 2021) - Killion, Alexander K.; Freedman, Eric; Neuzil, Mark
Abstract: In 2018, the U.S. National Park Service announced a controversial plan to translocate 20−30 gray wolves ( Canis lupus ) to Isle Royale National Park to increase genetic diversity and ultimately the dwindling wolf population. Media were restricted physical access during the translocations, citing safety concerns for the wolves and management team, as well as logistical challenges because of the remoteness of the park. Given these restrictions, we used interviews and quantitative analyses of news stories and press releases to examine what communication strategies the National Park Service and its partners deployed and how access restriction affected the way news outlets covered the events. By identifying source diversity groups, we found U.S. government sources were predominately featured with few other source types included, and that coverage heavily relied on press release information. We discuss the implications of this communication strategy and potential consequences for access restrictions when covering divisive events in remote locations.